2019
DOI: 10.4103/jovr.jovr_210_17
|View full text |Cite
|
Sign up to set email alerts
|

Detection of FZD4, LRP5 and TSPAN12 genes variants in Malay premature babies with retinopathy of prematurity

Abstract: Purpose: To determine the mutational analyses of familial exudative vitreoretinopathy (FEVR)-causing genes in Malay patients with retinopathy of prematurity (ROP) to obtain preliminary data for gene alterations in the Malay community. Methods: A comparative cross-sectional study involving 86 Malay premature babies (ROP = 41 and non-ROP = 45) was performed from September 2012 to December 2014. Mutation analyses in (FEVR)-causing genes ( NDP , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Additional features included microaneurysms, impaired hyaloid vessel regression, focal hemorrhages, retinal TSPAN12 variants can cause autosomal-dominant FEVR [57]. Variants of human TSPAN-12 have also been linked with ROP, specific types of cancer via regulation of progression, viral infections using TSPAN-12, and mental retardation [58][59][60]. Many variants identified in probands diagnosed with FEVR are predicted to result in a truncated protein, though studies were unable to perceive a difference in clinical presentation between patients with shortened proteins and those with missense mutations [57].…”
Section: Tspan-12mentioning
confidence: 99%
“…Additional features included microaneurysms, impaired hyaloid vessel regression, focal hemorrhages, retinal TSPAN12 variants can cause autosomal-dominant FEVR [57]. Variants of human TSPAN-12 have also been linked with ROP, specific types of cancer via regulation of progression, viral infections using TSPAN-12, and mental retardation [58][59][60]. Many variants identified in probands diagnosed with FEVR are predicted to result in a truncated protein, though studies were unable to perceive a difference in clinical presentation between patients with shortened proteins and those with missense mutations [57].…”
Section: Tspan-12mentioning
confidence: 99%
“…TSPAN12 variants can cause autosomal dominant FEVR [51]. Variants of human TSPAN-12 have also been linked with ROP, specific types of cancer via regulation of progression, viral infections using TSPAN-12, and mental retardation [52][53][54]. Many variants identified in probands diagnosed with FEVR are predicted to result in a truncated protein, though studies were unable to perceive a difference in clinical presentation between patients with shortened proteins and those with missense mutations [51].…”
Section: Tspan-12mentioning
confidence: 99%
“…Oxygen-induced retinopathy (OIR) phenotypes in rodent models also revealed proof of genetic effects, with discrepancies in retinal avascular areas and VEGF expression found between different rat strains [ 6 – 8 ]. An increasing number of researchers have reported that multiple genes are involved in predisposition to ROP in animal models and humans, and numerous candidate gene-related studies have been performed [ 9 13 ]. However, which genes are crucially and closely correlated with ROP is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have used microarray data profiles to illustrate the pathogenesis of ROP [ 9 14 ], but these studies were based on only a single cohort or single genetic event. To overcome this inadequacy, a comprehensive combination of gene expression profiling techniques and integrative bioinformatics approaches should be performed.…”
Section: Introductionmentioning
confidence: 99%